FEATURES OF LABOR COURSE IN OLIGOHYDRAMNIOS COMPARED WITH PHYSIOLOGICAL PREGNANCY: CLINICAL AND THEORETICAL ANALYSIS (International journal of medical sciences, 2026)
Oligohydramnios is a pathological condition of pregnancy characterized by a decrease in the volume of amniotic fluid below physiological norms. Amniotic fluid plays a crucial role in ensuring normal intrauterine fetal development, maintaining the homeostasis of the intrauterine environment, and providing optimal conditions for the course of labor. A reduction in its volume may significantly affect the course of pregnancy, labor, and perinatal outcomes. The aim of this study is to conduct a theoretical and analytical investigation of the characteristics of labor in cases of oligohydramnios compared with physiological pregnancy based on modern scientific data and statistical indicators presented in international and national scientific publications. This study presents a comprehensive analysis of the clinical and theoretical aspects of the influence of oligohydramnios on the course of labor. The pathophysiological mechanisms leading to decreased amniotic fluid volume are examined, as well as the impact of this condition on uterine contractile activity, the dynamics of cervical dilation, and the overall progression of the labor process. Particular attention is paid to obstetric complications, including uterine inertia, fetal distress, increased rates of operative delivery, and disorders of placental circulation. The analysis of statistical data demonstrates that the incidence of oligohydramnios averages between 1% and 5% of all pregnancies, while the risk of complicated labor in this category of patients is significantly higher compared with physiological pregnancy. In particular, an increased frequency of cesarean section, fetal hypoxia, and intrauterine growth restriction has been observed. The obtained theoretical conclusions confirm that timely diagnosis and rational obstetric management of pregnancy complicated by oligohydramnios are key factors in reducing perinatal complications. The results of the study can be used to improve clinical approaches to the management of labor in pregnant women with this pathological condition.